Structural and optical properties of nanostructure CdZnO films - Gupta, R. K.; Cavas, M.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
CdZnO thin films with different ratio of CdO and ZnO (3:1, 1:1, and 1:3) were grown on glass substrate using sal-gel spin coating method. The morphology of the CdZnO films depends on the amount of ZnO and CdO in the films. The optical band gap of the CdZnO films depends on the compositions of CdO and ZnO. Films having higher amount of CdO shows the presence of grains along with the fiber nature of ZnO, whereas the film with lower percentage of CdO shows fiber nature of the film very similar to pure ZnO film. The optical bandgap of CdZnO (3:1), CdZnO (1:1), and CdZnO (1:3) films was calculated to be 2.80, 2.49, and 2.52 eV, respectively. Other optical properties such as refractive index, extinction coefficient. and dielectric constants were calculated using the optical data. The volume and surface energy loss functions were also calculated and observed to increase with increase in the photon energy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CdO; ZnO; Sol-gel; Bandgap; Optical constants